IMPLEMENTASI APLIKASI CHATBOT SEBAGAI MEDIA INFORMASI PADA PENGEMBANGAN SISTEM AKADEMIK UNIVERSITAS ISLAM NEGERI (UIN) RADEN FATAH PALEMBANG MENGGUNAKAN ARTIFICIAL INTELLIGENCE MARKUP LANGUAGE (AIML) - Fenny Purwani; Ratih Tarina Utami Putri; Ilmia Tanjung; Salya Amiria Yuska (Jurnal Riset Teknik Komputer, 2024)
The development of information technology has impacted various sectors, including education, where quick and accurate access to academic information is a critical need for students. Universitas Islam Negeri (UIN)  Raden Fatah Palembang faces challenges in delivering academic information, such as the procedure for course registration (KRS), student enrollment, class schedules, and scholarships, which are often slow and difficult to access through traditional methods. To address these issues, this research aims to develop a chatbot application based on Artificial Intelligence Markup Language (AIML) that can provide academic information automatically, quickly, in real-time, and responsively. Using the Prototype Method, this system is expected to enhance the efficiency of academic information services at Universitas Islam Negeri (UIN) Raden Fatah Palembang, enabling it to respond to students' inquiries quickly, in real-time, and accurately.